2020
DOI: 10.1182/blood.2019004143
|View full text |Cite
|
Sign up to set email alerts
|

Oral cedazuridine/decitabine for MDS and CMML: a phase 2 pharmacokinetic/pharmacodynamic randomized crossover study

Abstract: This phase 2 study was designed to compare systemic decitabine exposure, demethylation activity, and safety in the first 2 cycles with cedazuridine 100 mg/decitabine 35 mg vs standard decitabine 20 mg/m2 IV. Adults with International Prognostic Scoring System intermediate-1/2- or high-risk myelodysplastic syndromes (MDS), or chronic myelomonocytic leukemia (CMML) were randomized 1:1 to receive oral cedazuridine/decitabine or IV decitabine in cycle 1, followed by crossover to the other treatment in cycle 2. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
143
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(146 citation statements)
references
References 24 publications
3
143
0
Order By: Relevance
“…Stated another way, doseescalations of decitabine or 5-azacytidine are not a solution for resistance since this compromises therapeutic-index: AML cells indefinitely self-replicate/proliferate and therefore have the opportunity to be educated for resistance from repeated treatment exposures, but normal myelopoiesis proliferates and terminally differentiates in successive waves-each wave is treatment naïve and vulnerable to offtarget anti-metabolite effects of high doses. The clinical tools to translate these preclinical observations are available, since combination formulations of decitabine with the CDA inhibitors THU or cedazuridine (a THU analog) are in clinical trials [4,40,53]; these oral drugs can produce lower decitabine C max but longer half-life than with approved intravenous regimens of decitabine, to deplete DNMT1 without cytotoxicity and facilitate frequent-distributed ingestion, as well as counter auto-upregulation of CDA [4,40].…”
Section: Discussionmentioning
confidence: 99%
“…Stated another way, doseescalations of decitabine or 5-azacytidine are not a solution for resistance since this compromises therapeutic-index: AML cells indefinitely self-replicate/proliferate and therefore have the opportunity to be educated for resistance from repeated treatment exposures, but normal myelopoiesis proliferates and terminally differentiates in successive waves-each wave is treatment naïve and vulnerable to offtarget anti-metabolite effects of high doses. The clinical tools to translate these preclinical observations are available, since combination formulations of decitabine with the CDA inhibitors THU or cedazuridine (a THU analog) are in clinical trials [4,40,53]; these oral drugs can produce lower decitabine C max but longer half-life than with approved intravenous regimens of decitabine, to deplete DNMT1 without cytotoxicity and facilitate frequent-distributed ingestion, as well as counter auto-upregulation of CDA [4,40].…”
Section: Discussionmentioning
confidence: 99%
“…Three azanuclesoides are approved for MDS: 5‐azacitidine (azacitidine) 81 5‐aza‐2′‐deoxycitidine (decitabine) 82 and, in 2020, ASTX727 (decitabine and cedazuridine) 83 . Azacitidine is approved for all subsets of MDS, whereas decitabine is approved for those with intermediate‐1 disease and above.…”
Section: Risk Adapted Therapymentioning
confidence: 99%
“…Decitabine was studied in an initial randomized trial comparing it to BSC 82 . In this study, the dose of decitabine was 15 mg/m 2 IV infused over 3 hours every 8 hours for 3 days (at a dose of 135 mg/m 2 per course) and repeated every 6 weeks.…”
Section: Risk Adapted Therapymentioning
confidence: 99%
“…In a recent phase 2 study, 80 patients with intermediate-1/2- or high-risk MDS or chronic myelomonocytic leukemia (CMML) were randomized to receive ASTX727 or IV decitabine, with crossover occurring in cycle 2. 103 Clinical responses were observed in 48 patients (60%) including 17 (21%) with complete response. The study showed that the efficacy, side effect profile, and systemic decitabine exposure of ASTX727 are similar to that of IV decitabine, and it was approved by the FDA in July 2020 for IPSS intermediate-1, intermediate-2, and high-risk MDS.…”
Section: Emerging Therapeutics For Management Of Anemia In Lr-mdsmentioning
confidence: 97%